A non-equivalent group pilot trial of a school-based physical activity and fitness intervention for 10-11 year old english children: born to move - Stuart J. Fairclough; Bronagh McGrane; George Sanders; Sarah Taylor; Michael Owen; Whitney Curry (BMC, 2016)
Abstract Background PE lessons are the formal opportunity in schools for promotion of physical activity and fitness. This study aimed to evaluate the effectiveness of a pilot PE intervention on physical activity, fitness, and psychosocial outcomes. Methods Participants were 139 children aged 10-11 years from four schools. For six weeks children in two schools received a twice-weekly pilot 'Born to Move' (BTM) physical activity (PA) and fitness intervention alongside one regular PE lesson. Children in the two comparison (COM) schools received their regular twice weekly PE lessons. Outcomes were lesson time and whole-day light (LPA), moderate (MPA), vigorous (VPA), and MVPA, and sedentary time, muscular fitness, cardiorespiratory fitness (CRF), and lesson-specific perceived exertion, enjoyment, and perceived competence. Outcomes were assessed at baseline (T0), midway through the intervention (T1), and at the end (T2) using ANOVAs and ANCOVAs. Intervention fidelity was measured using child and teacher surveys at T2 and analysed using Chi-square tests. Results The BTM group engaged in moderate PA for significantly more lesson time (29.4 %) than the COM group (25.8 %; p = .009, d = .53). The amount of moderate-to-vigorous PA (MVPA) during the T1 BTM lesson contributed 14.0 % to total MVPA, which was significantly more than the COM group's T1 PE lesson (11.4 %; p < .001, d = .47). The BTM group were significantly more active during the whole-day (p < .05) and the school-day (p < .01). In both groups push-up test performance increased (p < .001) and CRF test performance decreased (p < .01). Perceived exertion, enjoyment, and perceived competence increased in both groups (p < .05), but the BTM group rated their enjoyment of the T1 BTM lesson higher than the COM group rated their PE lesson (p = .02, d = .56). The children's and teachers' responses to the intervention indicated that the delivery aims of enjoyment, engagement, inclusivity, and challenge were satisfied. Conclusions The BTM pilot programme has potential to positively impact on physical activity, fitness, and psychosocial outcomes. Further, BTM was enjoyed by the children, and valued by the teachers. This study can inform the design of a modified larger-scale cluster RCT evaluation.